Adventitious Plantlet Formation In Bambusa tulda – A New Report - BORAH, ELLORA DUTTA; HAZARIKA, PRODIP KR.; PRADHAN, BIJOY; JAYARAJ, R.S.C. (Indian Forester, 2023)
The paper documents an unusual formation of above ground rhizome in the culms of Bambusa tulda, effectively serving as an adventitious plantlet. From the survey of review of literature, it is found that there is no report on formation of adventitious plantlet in B. tulda and this seems to be the new report .